Research Progress on WC-12Co Coatings Prepared by High Velocity Oxy-Fuel Spraying - SI Yongli, NAN Jian, XIE Liangjun, SONG Shengqiang, DAI Xueting, MU Zhigang, ZOU Junwen (Cailiao Baohu)
High velocity oxy-fuel (HVOF) spraying has been developed as an important technology in surface engineering and remanufacturing to provide materials with protective and functional coatings，thereby ensuring the surface protection of parts and the remanufacturing of damaged products.The preparation of WC-12Co coatings by high velocity oxy-fuel (HVOF) is of great significance in improving the surface wear resistance of substrate materials and prolonging the service life of parts.In this paper， the spray powder， preparation process， control of coating microstructure and properties， flow field numerical simulation， particle deposition behavior， surface protection of engineering materials and posttreatment of HVOF spraying WC-12Co coatings were summarized.The research trends and application prospects of WC-12Co coatings were also prospected， and it was proposed that the evaluation of coating properties and protection， numerical simulation and experimental verification of the spraying process， and engineering application research were worthy of continuous attention.